Some machnical and thermal proprties of mullite prepared from iraqi starting materials (Baghdad Science Journal, 2005)
Some mechanical and thermal properties of mullite samples prepared by mixing different phases of alumina and silica powders have been studied according to ASTM methods the cold crushing strength of the sintcred bodies.With different porosity, at room temperature was in the range(18-54)Mpa